2017
DOI: 10.1080/08870446.2017.1401623
|View full text |Cite
|
Sign up to set email alerts
|

How can the health belief model and self-determination theory predict both influenza vaccination and vaccination intention ? A longitudinal study among university students

Abstract: Background and objective Seasonal influenza is frequent among students and often responsible for impaired academic performance and lower levels of general health. However, the vaccination rate in this population is very low. As the seasonal influenza vaccine is not compulsory in France, it is important to improve the vaccination uptake by identifying predictors of both intention and behaviour. This study investigated the effect of decisional balance, motivation and self-efficacy on vaccination acceptance using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
113
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(124 citation statements)
references
References 53 publications
9
113
0
2
Order By: Relevance
“…Another finding of the present study was that HBMbased family-centered education was effective in fostering parents' positive attitude towards healthcare providers' recommendations and their perceptions about the benefits of such recommendations. Similarly, a former study reported that HBM-based education positively affected behaviors related to influenza vaccination (23). Therefore, in their educational programs for children with chronic conditions (such as asthma) and their parents, healthcare providers need to focus on the benefits of behavior modification.…”
Section: Discussionmentioning
confidence: 99%
“…Another finding of the present study was that HBMbased family-centered education was effective in fostering parents' positive attitude towards healthcare providers' recommendations and their perceptions about the benefits of such recommendations. Similarly, a former study reported that HBM-based education positively affected behaviors related to influenza vaccination (23). Therefore, in their educational programs for children with chronic conditions (such as asthma) and their parents, healthcare providers need to focus on the benefits of behavior modification.…”
Section: Discussionmentioning
confidence: 99%
“…Such results were not unexpected. On the one hand, the Health Belief Model points out that personal experiences and knowledge status are the logical prerequisites to raise risk perception, which in turn promotes behavioral adaptations [ 22 , 28 ]. On the other hand, Occupational Physicians acknowledging TBE as a severe disease were less frequently promoting TBE vaccine among high-risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Occupational Physicians acknowledging TBE as a severe disease were less frequently promoting TBE vaccine among high-risk groups. These results may appear as inconsistent, or even openly in opposition with the basic assumption that a better understanding of the risk associated with a certain disorder will ultimately increase the acceptance of countermeasures [ 22 , 28 ], but it should be stressed that with an overall annual incidence of 0.1 cases/100,000 people, TBE remains an uncommon event for the majority of professionals not working in high-risk areas [ 1 , 2 , 3 , 4 , 5 ]. Previous studies on KAP of Italian OP have shown significant knowledge gaps and misunderstandings on up-to-date vaccinology [ 18 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,[11][12][13] Health care providers create promotional health information resources to educate and encourage behavior change in parents and patients. [14][15][16][17] The content and wording of educational handouts are important to examine carefully. For example, pro-vaccine educational handouts attempting to disprove myths or change parental views may reduce measles-mumps-rubella vaccination intention among parents who are vaccine hesitant.…”
mentioning
confidence: 99%